2016
DOI: 10.1177/0265813515607474
|View full text |Cite
|
Sign up to set email alerts
|

Wind and the city: An evaluation of San Francisco’s planning approach since 1985

Abstract: In 1985, San Francisco adopted a downtown plan on ground-level wind currents intended to mitigate the negative effects of wind on pedestrians' perceived comfort in public open spaces. The plan mandates that new buildings in designated parts of the city associated with high density or development potential be designed or adopt measures to not cause wind in excess of accepted comfort levels. This study examines whether and to what degree the plan has successfully shaped an urban form that mitigates wind by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…For Only Wind Murota [16] Kobayashi et al [17] Ishizaki et al [18] Kim, H et al [15] Meng, X et al [19] Bosselmann et al [20] Arens et al [21] For Wind and Snow…”
Section: Building Design Urban Designmentioning
confidence: 99%
See 3 more Smart Citations
“…For Only Wind Murota [16] Kobayashi et al [17] Ishizaki et al [18] Kim, H et al [15] Meng, X et al [19] Bosselmann et al [20] Arens et al [21] For Wind and Snow…”
Section: Building Design Urban Designmentioning
confidence: 99%
“…Anno [22] Smedley et al [23] Yukawa et al [24] Mitsuhashi [25] Yukawa et al [26] Setoguchi et al [27][28][29][30][31][32] Watanabe et al [33] Kim et al [15], Meng et al [19], Bosselmann et al [20] and Arens et al [21] produced useful studies of downtown San Francisco, California, United States, and they demonstrated the environmental impact of high-and mid-rise buildings using wind simulations conducted solely using a wind tunnel which compared San Francisco's wind conditions in 1985 and 2013 using a wind tunnel [15,[19][20][21]. Kim et al [15] suggested that the planning guidelines enacted since 1985 were effective in improving the wind comfort in public spaces.…”
Section: Building Design Urban Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Bosselmann et al studied downtown San Francisco, California, USA and showed, by simulation using a wind tunnel, that new high-rise developments are causing environmental problems resulting from changes in wind and sunlight conditions [4,5]. Kim and Macdonald compared San Francisco's wind environments in 1985 and 2013, and showed the effect of controlling urban forms in the wind environment using a wind tunnel [6]. Tomabechi et al simulated the effect of snow with a wind tunnel [7].…”
Section: Urban-design Process With Snow and Wind Simulations: A Studymentioning
confidence: 99%